2002
DOI: 10.1080/01926230252929918
|View full text |Cite
|
Sign up to set email alerts
|

Acute Changes in Lung Histopathology and Bronchoalveolar Lavage Parameters in Mice Exposed to the Choking Agent Gas Phosgene

Abstract: Phosgene (CG) is a highly irritant gas widely used industrially as a chemical intermediate for the production of dyes, pesticides, and plastics, and can cause life-threatening pulmonar y edema within 24 hours of exposure. This study was designed to investigate acute changes in lung tissue histopathology and selected bronchoalveola r lavage uid (BALF) factors over time to determine early diagnostic indicators of exposure. Three groups of 40 male mice each were exposed to 32 mg/m 3 (8 ppm) CG for 20 minutes, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(36 citation statements)
references
References 21 publications
3
33
0
Order By: Relevance
“…Our previously published proteomics data demonstrated the overexpression of SPLUNC1 in the lungs of mice after repeated exposures to SWCNTs (32), suggesting that the up-regulation of SPLUNC1 is a feature of the innate immune response to environmental foreign particles. In the present study, an 80-mg bolus of SWCNTs per mouse was delivered by pharyngeal aspiration to the mice.…”
Section: Discussionmentioning
confidence: 99%
“…Our previously published proteomics data demonstrated the overexpression of SPLUNC1 in the lungs of mice after repeated exposures to SWCNTs (32), suggesting that the up-regulation of SPLUNC1 is a feature of the innate immune response to environmental foreign particles. In the present study, an 80-mg bolus of SWCNTs per mouse was delivered by pharyngeal aspiration to the mice.…”
Section: Discussionmentioning
confidence: 99%
“…research on countermeasures to mitigate phosgene-induced ALI in controlled animal models has been published (Sciuto et al, 1995(Sciuto et al, , 1996Sciuto, 1997;Duniho et al, 2002;Sciuto and Hurt, 2004).…”
mentioning
confidence: 99%
“…Because of its insoluble nature, phosgene attacks the deeper regions of the lung where it can alter the GSH redox enzymes (42). Furthermore, phosgene has been shown to increase lipid peroxidation, cause the release of sulfidopeptide leukotrienes, alter important cell ultrastructures, and react directly with lung surfactant (22,24,27,43). In addition, it has been shown that phosgene can form adducts with renal microsomal phospholipid polar heads (19).…”
Section: Resultsmentioning
confidence: 99%